Sensitive hospitalizations to primary care and care in the health care network - Pollyanna Kássia de Oliveira Borges; Paola Martins Schawb; Clóris Regina Blanski; Lara Simone Messias Floriano; Beatriz Gonçalves Lopes; Erildo Vicente Muller (Universidade Federal do Ceará, 2016)
Objective: to check the profile of sensitive causes hospitalizations for primary care. Methods: this is an ecological, epidemiological study. Data was collected in the Hospital Information System at the Department of Health System Information, grouped according to the admissions list for Sensitive to Primary Causes of Health System. Results: there were 227,014 hospitalizations, 25.8% of them were sensitive to Primary care. The illnesses which caused sensitive admissions were pneumonia (n=19,832; 33.7%), heart failure (n=6,688, 11.3%), and gastroenteritis (n=6,287, 10.7%). Conclusion: sensitive hospitalizations for primary care have decreasing historical trend in the study area. Primary care services, with guidelines and principles, well conducted could minimize the risk of exacerbation of chronic conditions and also endorse lower rates of infection transmitted diseases.